Acetylcholinesterase: Inhibitory activity of some Indonesian vegetables and fraction of selected plants - Maulita Cut Nuria&, Asep Gana Suganda, Elin Yulinah Sukandar, Muhamad Insanu (Journal of Applied Pharmaceutical Science, 2020)
Dementia is a global health problem that requires severe treatment. People with dementia who consume vegetables every day can reduce the risk of dementia. Alzheimer’s is one of the diseases that are characterized by dementia, which results in decreased neurotransmitter acetylcholine. This study was to investigate the acetylcholinesterase (AChE) enzyme inhibitory activity of various vegetables that are widely used by Indonesian Sundanese and Javanese ethnics. In this study, total phenolic and flavonoid content were analyzed for the determination of active compounds of the extracts. Ethanol extracts of 13 vegetables have been tested for AChE inhibitory activity using Ellman's colorimetric method in 96-well plate. Four types of extracts (Cosmos caudatus, Nasturtium officinale, Nothopanax fruticosus, and Ocimum americanum) had higher total phenolic and flavonoid content than other extracts. Vegetable extracts that had IC50 values of less than 1,000 μg/ml were C. caudatus and O. americanum. Both of these extracts were partitioned with n-hexane and water. The IC50 values of water fraction of C. caudatus and n-hexane fraction of O. americanum were 325.0 ± 18.3 and 374.4 ± 42.1 μg/ml, respectively. These results showed that fractions had a potential inhibitor of AChE, and the chemical components (phenolic, flavonoid, and terpenoid) can be isolated to find the active compound.
Keywords: Acetylcholinesterase, flavonoid, phenolic, vegetables.